Karakteristik Penderita Pneumonia Usia 1-59 Bulan yang Dirawat Inap di Rumah Sakit - Made Kristya Pitaloka Gangga Dewi; Anak Agung Oka Lely; Anak Agung Ayu Lila Paramasatiari (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Pneumonia is an acute infectious ailment affecting the pulmonary parenchyma and caused by bacteria, viruses, or fungi. Denpasar stood out among the regions in Bali with the highest occurrence of pneumonia cases among children below the age of five, with a total of 631 individuals in 2021. The aim of this research is to establish the attributes of hospitalized pneumonia patients aged 1 to 59 months at Surya Husadha General Hospital Denpasar from 2020 to 2022. This study adopts a descriptive approach with a cross-sectional design. Data were procured through the utilization of complete sampling technique, involving 81 patients medical records. The results showed that the majorities of pneumonia patient were aged 1 - 23 months as many as 42 children (51.9%), 48 children (59.3%) were male, and 69 children (85.2%) had good nutritional status. All toddlers who became research subjects had received complete basic immunization, 90.1% of them were categorized as pneumonia and 67.9% of toddlers underwent hospitalization with a lengths of stay of more than five days. This indicates that toddlers with pneumonia who were hospitalized were mostly <2 years old, male, with good nutritional status, and had received complete basic immunization. Most toddlers did not suffer from severe pneumonia with an average length of stay of 5 days.